Microfluidic platform for continuous flow synthesis of triangular gold nanoplates - Kumar, D. V. Ravi; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2014)
A microfluidic platform for the continuous flow synthesis of triangular gold nanoplates with and without surfactants is developed. The temperature profile in the microchannel, residence time and composition have been studied to understand effect of these parameters on the yield of the triangular nanoplates and were optimized for obtaining maximum yield of triangles. The flow synthesis approach has been demonstrated where the Br- ions can be supplied to the reaction mixture either from the surfactant viz. Cetyl trimethylammonium bromide (CTAB) or even from HBr. Apart from the Br- ions, the temperature gradient at the inlet of the continuous flow reactor is one of the key parameter that affects the yield of the triangular nanoplates. Finally we establish that with a right combination of the controlling parameters abetter yield of the Au nanotriangles by flow methods can be achieved even in the absence of surfactant. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Au nanotriangles; Flow synthesis; microreactor; Nucleation kinetics; Surfactants